Menganalisis Keberhasilan Provinsi Kepulauan Riau Pasca Pemekaran Daerah di Bidang Ekonomi dan Infrastruktur (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
This study analyzes the success of the Riau Islands Province post-regional expansion in the fields of economy and infrastructure. The territorial expansion carried out in 2002 aimed to enhance government efficiency and accelerate regional development. Despite notable progress, such as economic growth exceeding the national average and controlled inflation, significant challenges remain, including dependency on transfers from the central government. The Fiscal Independence Index (IKF) indicates that most districts and cities in Riau Islands Province are still categorized as "Not Independent." Therefore, a comprehensive strategy is needed to increase Regional Original Income (PAD) and strengthen fiscal decentralization. The method used in this study is literature review, which involves examining and analyzing written sources such as books, articles, and academic journals. Through this method, researchers can gather relevant information and understand the context and developments in the studied field. This research also provides policy recommendations to enhance community participation in decision-making, aiming for more effective regional autonomy. Thus, this study is expected to contribute to the literature on regional expansion and local government policies in Indonesia.